Implicações decorrentes das diferenças de gênero para a prática de professores do sexo masculino na educação infantil - REIS, Gabrielly Gomes dos (2019)
The present research aims at analyzing how gender conceptions are constructed in contemporary society in order to understand how the feminine and masculine meanings historically constructed to the teaching profession imply in the pedagogical practice of male teachers in the context of Early Childhood Education. For this purpose, two teachers and two school administrators from the municipality of Castanhal – PA, were interviewed, challenging, in the light of their reports, some prejudiced conceptions that are justified in the gender differences to determine men and women within the labor market. Raising on the basis of feminist and gender studies, a non-sexist education, aimed at the deconstruction of stereotypies that further attenuate gender inequalities, thus seeking subsidies capable of orienting us on the need to consider the relational character of both the man / teacher and of the woman / teacher in education, understanding that both can contribute in their own way to the teaching-learning process, giving them the right to occupy places / positions / functions according to their personal and professional perspectives, regardless of gender or other.